Climate-smart villages and progress in achieving household food security in Lushoto, Tanzania - Recha, John W.M.; Radeny, Maren A.O.; Kinyangi, James; Kimeli, Philip; Atakos, Vivian; Lyamchai, Charles; Ngatoluwa R; Sayula, George (2015)
Preliminary results from climate change adaptation and mitigation initiatives in Lushoto climate-smart villages, Tanzania.